The Concept of Ndalem as Manifestation of Sufistic Values and Practice of Kiai Kampung in Madura - Nurul Qomariyah; Fathorrozy (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
This study explores ndalem, the residence of kiai kampung (village kiai) in Madura, as an embodiment of Sufistic values and practices. Using a descriptive qualitative approach through historical analysis, ethnography, and interviews, this research examines the historical roots of Sufism in Madura, the role of kiai in Sufi practices, as well as the architectural and symbolic elements of ndalem as a spiritual and cultural space. The findings indicate that the ndalem serves as both a residence for the kiai and a place where social and religious activities of the kiai, santri, and the religious community take place. The history and background of Sufism in Madura point to the character of kiai kampung as religious leaders in rural areas who play crucial roles in spreading and revitalizing Sufi teachings among society. The structure of ndalem, as a place of kiai to dwell, reflects Sufistic values, particularly those that embody deep spirituality. One of the essential aspects is the preservation of dikr (remembrance of God) and wirid (spiritual recitations). Kiai kampung also plays a key role in maintaining these traditions among the Madurese community. Contribution: This study contributes to capturing the Sufistic expression in spatial space, besides social and ritual practices, as part of Living Sufism.